Effects of environment factors on the occurrence of blossom-end rot in soilless cultured Capsicum fructescens var. grossum - LI Guo-jing; Benoit F; Ceustermans N (浙江大学学报. 农业与生命科学版, 2003)
Blossom-end rot (BER), a physical disorder common in tomato and pepper fruits, is related to calcium deficiency in the fruits. To investigate the effects of air humidity, slab temperature and slab moisture on the incidence of BER in soilless cultured sweet pepper, a series of experiments have been carried out within three years. There were 12 treatments, included air humidity enrichment to 60%, air humidity control environment; slab cooling to 17 ℃, control; slab moisture controlled by timer, set at 50%, set at 60%. The results showed that air humidity enrichment buffered the acute daily change of the air relative humidity and the air temperature in the greenhouse, especially during a hot day. The number of vascular bundles in the fruit parts was significantly increased under the humid conditions, and a much higher increase was found in the distal part of the fruit than that in the basal part, with 14.6% and 11.4% increase relative to the control plants respectively. The Ca levels were significantly higher in the fruits developed under the humidity enrichment conditions, with 19.9% more in the basal part and 16.6% more in the distal part than that in the control. However, the K content is quite stable both in the fruits and in the leaves. Slab cooling resulted in higher oxygen content in the root environment, which improved root activity. It was clear that air humidity enrichment, slab cooling as well as slab moisture 50% significantly lowered the incidence of BER. And there was positive cumulative effect of air humidity enrichment, slab cooling and slab moisture on the occurrence of BER in soilless cultured sweet pepper. But no explicitly significant differences of the harvested fruit number and the yield were observed among the different treatments throughout the growing season.